ダイ11ジ ナンキョク チイキ カンソクタイ ロケット ブモン ホウコク - 川口, 貞男; カワグチ, サダオ; 平沢, 威男; ヒラサワ, タケオ; 伊東, 弘二; イトウ, ヒロジ; 芦田, 成生; アシダ, シゲオ; 鮎川, 勝; アユカワ, マサル; 白壁, 弘保; シラカベ, ヒロヤス; et al. (国立極地研究所, 1971)
P(論文) The rocket launching facilities were constructed at the Japanese Antarctic base, Syowa Station (69°00'S, 39°35'E : geomagnetic lat. 69.6°S, long. 77.1°E) in January 1970. On the 10th and 17th of February, 1970, the two launching experiments of sounding rockets were carried out. Through the successful rocket flight, the reasonable vertical profiles of electron and ozone density in the polar ionosphere were obtained. 1. Rocket Launching Facilities at Syowa Station In the rocket range, about 500m south-west of the main base of Syowa Station, there are three huts, namely, an assembly shop connected with a turn table, a Radar-Telemeter hut and the control center. The rocket is assembled and tested in the assembly shop, and transferred to the turn table on the launcher. The Radar-Telemeter Hut contains a radar-telemeter system and an igniter controler. Probe parts of rockets are assembled and tested in this hut. In the control center, there is a seat for the commander of the rocket experiments. The whole system is capable of launching the single-stage rocket, S-160JA type (length 3890mm, diameter 160mm, pay-load 5.4kg, max. altitude 88km), S-210JA type (5210mm, 210mm, 12kg, 120km), S-300JA type (diameter 300mm, max. altitude 160km) and S-350JA type (diameter 350mm). 2. Results of Observation 2. 1. Electron density The electron densityprofiles in the ionosphere D-region obtainedby the present rocket experiments are illustrated. The first rocket (JA-1) was launched in a magnetically quiet condition, and the second (JA-2) during a small positive bay 40 γ with an ionospheric absorption of 0.5 dB. The N-h profile obtained by JA-2 shows about 3 × 10^3 - 2 × 10^4 ele/cm^3 higher than that by JA-1 in the 78-87km height range. These facts suggest that the energetic electrons (or protons) with an energy of about 100keV (or 1 MeV) penetrate down to the 70-90km height in the polar ionosphere with a flux of about 10^6ele/cm^2/s to enhance the D- and lower E-region ionization during the positive-bay event in the daytime. 2. ...